Encapsulation of indocyanine green in poly(lactic acid) nanofibers for using as a nanoprobe in biomedical diagnostics - YILMAZ, BETÜL; OKTAR, FAİK NÜZHET; GÜNDÜZ, OĞUZHAN (ELSEVIER, 2018)
Some chronic illnesses do not show any symptoms at an early stage, which causes a difficult to treating the situation. Especially cardiovascular diseases, liver functions and cancer could be prevented at early stages of diseases by advanced biomedical imaging techniques. In this study, indocyanine green (ICG), which must be stabilized in aqueous media for the development of its use in biomedical applications, was stabilized by encapsulating into the biodegradable polymer of poly(lactic acid) (PLA) using a coaxial electrospinning (CES) method to produce ICG near infrared (NIR) fluorophore nanoprobe with the one-step process. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Indocyanine green; Biomedical imaging; Poly(lactic acid); Coaxial electrospinning; Controlled release